SCIENTIFIC RESEARCH ON THE ANTI-STRESS PREPARATION OF SPECIALISTS IN A QUARTER CENTURY - Hryshchenko, Yuriy (Proceedings of National Aviation University (archive), 2014)
This article provides an analytical overview of the work on training of human operator counteract the simultaneous action of negative factors, carried out by experts from the Avionics Department. The focus is on the method of training of operators by removing the negative effects of the flight, which are associated with the phenomenon of amplification of the dynamic stereotype in aviation specialists. It should be noted that the author does not fully cover all the anti-stress training methods that have been developed by our experts